2018
DOI: 10.1177/2047487318759694
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum potassium concentration with mortality and ventricular arrhythmias in patients with acute myocardial infarction: A systematic review and meta-analysis

Abstract: Background Challenging clinical practice guidelines that recommend serum potassium concentration between 4.0-5.0 mEq/L or ≥4.5 mEq/L in patients with acute myocardial infarction, recent studies found increased mortality risks in patients with a serum potassium concentration of ≥4.5 mEq/L. Studies investigating consequences of hypokalemia after acute myocardial infarction revealed conflicting results. Therefore, the aim of this systematic review and meta-analysis was to combine evidence from previous studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
3
22
0
4
Order By: Relevance
“…Our findings are in line with results of a recent systematic review, investigating the association of potassium concentration with mortality and occurrence of ventricular arrhythmias in patients after myocardial infarction in 12 studies. In those cardiac risk patients, they found an increased mortality risk when potassium concentrations were above 4.5 mmol/l [12]. In agreement, in patients with atrial fibrillation, we observed the lowest mortality when mean potassium was > 3.5–4.0 mmol/l.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings are in line with results of a recent systematic review, investigating the association of potassium concentration with mortality and occurrence of ventricular arrhythmias in patients after myocardial infarction in 12 studies. In those cardiac risk patients, they found an increased mortality risk when potassium concentrations were above 4.5 mmol/l [12]. In agreement, in patients with atrial fibrillation, we observed the lowest mortality when mean potassium was > 3.5–4.0 mmol/l.…”
Section: Discussionsupporting
confidence: 88%
“…In summary, previous guidelines recommend potassium concentrations rather in the upper normokalaemic range. However, there is evidence that potassium concentrations above 4.5 mmol/l may be adversely associated with survival in patients with myocardial infarction [8, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Sudden cardiac death (SCD), mostly due to ventricular tachyarrhythmias (VTs), contributes to ~50% of HF deaths (Tomaselli and Zipes, 2004 ). Hypokalemia is a well-recognized risk factor for VT, and hypokalemia is both common and independently associated with worse clinical outcomes in HF patients (Cleland et al, 1987 ; Ahmed et al, 2007 ; Bowling et al, 2010 ; Kjeldsen, 2010 ; Aldahl et al, 2017 ; Nunez et al, 2018 ), as well as increasing the risk of ventricular arrhythmias and mortality during acute myocardial infarction (Goyal et al, 2012 ; Colombo et al, 2018 ; Hoppe et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypokalemia is known to increase the risk of supraventricular and ventricular arrhythmias, especially when serum potassium is <3.5 mEq/L [7][8][9][10]. A large cohort of 2.6 million patients found that hypokalemia was significantly associated with a 2-fold increased risk of in-hospital mortality among patients with a diagnosis of CHF, regardless of causes of hypokalemia [11].…”
Section: Introductionmentioning
confidence: 99%